On a Parabolic Variational Inequality That Generalizes the Equation of Polytropic Filtration - Buhrii, O. M.; Lavrenyuk, S. P. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We obtain conditions for the existence and uniqueness of a solution of a parabolic variational inequality that is a generalization of the equation of polytropic elastic filtration without initial conditions. The class of uniqueness of a solution of this problem consists of functions that increase not faster than e −μt , μ > 0, as t → −∞.